Theoretical Insights into Ammonia Production and Conversion via Heterogeneous Catalysis - Brennan, Kevin (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2024)
The global population is heavily dependent upon the production of ammonia via the Haber-Bosch process. This is an environmentally unfriendly process that demands pure hydrogen, obtained from the steam reforming of methane. As such there is an incentive to move to more sustainable procedures such as the electrochemical reduction of atmospheric nitrogen to ammonia. This process, however, is limited by the difficult activation of nitrogen, as well as competition with the evolution of hydrogen. We circumvent the first issue by reducing a different substrate that is an already fixed form of nitrogen, cyanide, towards methane and ammonia. The reduction of nitrates to ammonia serves as a proof of concept, and if the world intends to move to a circular economy, then investigating the reduction of cyanide is a necessity. This thesis begins by shedding light on the possible mechanisms of cyanide reduction through theoretical calculations. These reaction mechanisms serve as a foundation upon which we add layers of detail to our calculations, such as the inclusion of implicit and explicit solvation models, or the external applied potential. The final chapter of this thesis then delves into the photo-thermal decomposition of ammonia for chemical hydrogen storage. This is presented as a short-term solution to the energy crisis, wherein blue ammonia is still produced by the Haber-Bosch process and employed as an energy vector.
APPROVED
Keywords: Theoretical Chemistry; Ammonia; Cyanide; Density Functional Theory; Heterogeneous Catalysis